Tuberculosis incidence among infected contacts detected through contact tracing of smear-positive patients. - Mario Martin-Sanchez; Silvia Brugueras; Anna de Andrés; Pere Simon; Pilar Gorrindo; Miriam Ros; Eva Masdeu; Joan-Pau Millet; Joan A Caylà; Àngels Orcau; Contact Tracing Group of the Tuberculosis Investigation Unit of Barcelona (PLoS ONE, 2019)
Background The contacts of people with pulmonary tuberculosis (PTB) have a high risk of becoming infected and developing tuberculosis (TB). Our aim was to determine the incidence of TB and its risk factors in a cohort of contacts with latent TB infection (LTBI) detected through contact tracing of smear-positive PTB cases. Methods and findings We performed a population-based retrospective cohort study including contacts that had LTBI, and were contacts of people with PTB who started treatment between 2008 and 2014. We followed up contacts until they developed TB or until the end date for follow-up (31st December 2016). We used Kaplan-Meier curves to compute incidence at 2 and 5 years, and Cox regression to compute hazard ratios (HR) and their 95% confidence intervals (CI). We analyzed 3097 close contacts of 565 PTB cases. After exclusion of 81 co-prevalent TB cases, 953 contacts had LTBI, of which 14 developed TB. Their risk of developing TB after two and five years was 0.7% (CI: 0.3-1.6) and 1.8% (CI: 1.1-3.1) respectively. Contacts who had not been referred for LTBI treatment had a 1.0% (CI: 0.2-4.0) risk at 5 years. Risk of developing TB at 5 years was 1.2% (CI: 0.5-3.0) among people who completed treatment, and 11.1% (CI: 5.1-23.3) for those who did not. Risk factors for TB were not completing LTBI treatment (HR 9.4, CI: 2.9-30.8) and being female (HR 3.5, CI: 1.1-11-3). Conclusions LTBI treatment plays a fundamental role in decreasing the risk of developing TB. It is necessary to achieve a maximum contact tracing coverage and the highest possible compliance with LTBI treatment.